GP and pharmacist inter-professional learning – a grounded theory study. Issue 3 (3rd May 2016) - Cunningham, David E.; Ferguson, Julie; Wakeling, Judy; Zlotos, Leon; Power, Ailsa
Abstract: Background : Practice Based Small Group Learning (PBSGL) is an established learning resource for primary care clinicians in Scotland and is used by one-third of general practitioners (GPs). Scottish Government and UK professional bodies have called for GPs and pharmacists to work more closely together to improve care. Aim : To gain GPs' and pharmacists' perceptions and experiences of learning together in an inter-professional PBSGL pilot. Design and setting : Qualitative research methods involving established GP PBSGL groups in NHS Scotland recruiting one or two pharmacists to join them. Method : A grounded theory method was used. GPs were interviewed in focus groups by a fellow GP, and pharmacists were interviewed individually by two researchers, neither being a GP or a pharmacist. Interviews were audio-recorded, transcribed and analysed using grounded theory methods. Data saturation was achieved and confirmed. Results and conclusion : Three themes were identified: GPs' and pharmacists' perceptions and experiences of inter-professional learning; Inter-professional relationships and team-working; Group identity and purpose of existing GP groups. Pharmacists were welcomed into GP groups and both professions valued inter-professional PBSGL learning. Participants learned from each other and both professions gained a wider perspective of the NHS and of each others' roles in the organisation. Inter-professional relationships, communication and team-working were strengthened and professionals regarded each other as peers and friends.